Production Problems in Textile Industry with Special Reference to Karur District, Tamil Nadu - Rajasekar, N.; Gurusamy, M. (Indian Journal of Marketing, 2010)
The textile industry is the single largest foreign exchange earner for India. Currently, it accounts for about 8% of GDP, 20% of the industrial production and over 30% of export earnings of India and it has only 2-3% import intensity. About 38 million people are gainfully employed with the industry, making it the second largest employment providing sector after agriculture. The textile policy of 1985 and the economic policy of 1991 accelerated the economic growth during 1990's. Textile sector growth has been led by the spinning and the manmade fibre industry. The number of cotton/manmade fibre textile mills rose from 1035 in 87-88 to 1741 by December, 1997. The number of spinning mills rose to 1461 in December 1997 from 752 in 87-88. Liberalization led to the installation of open end rotors and setting up of Export Oriented Units (EOU). Currently, India has the second highest spindle age in the world after China. Aggregate production of cloth during 1996-97 was 34,265 million sq. meters, an increase of nine percent over 1995-96. India's contribution in world production of cotton textiles was about 12% a decade back, while currently, it contributes about 15% of world cotton textiles. The production of silk has increased from 9498 tonnes in 1987-88 to 14,093 tonnes in 1996-97. Wool, is another major raw material for which India depends on imports, especially from New Zealand, to meet its requirements. Growth rate in exports of textiles/clothing during 1996-97 was 11%. Introduction of a soft loan scheme during the 7th plan called Textile Modernization Fund Scheme (TMFS) facilitated the process of modernizing textile industry significantly. Indian textile industry has performed remarkably well during the last one decade, but it still needs to carve a competitive edge through quality output and high value addition, especially when India is on the fast track of globalization.